VALIDAÇÃO DAS ANÁLISES FÍSICO-QUÍMICAS EXIGIDAS PELA ANP PARA MISTURAS DIESEL – BIODIESEL - Folquenin, Elisiane Karam Folador (2008)
The use of Biodiesel as an additive to diesel in automotive proportion of 2 % v/v is being marketed in Brazil since January 2008. Thus, it is extremely important Know the environmental and commercial impact of samples of B100 produced and mixtures, for example, B2 (stipulated by the ANP - the National Petroleum Agency). The objective this paper is to physical-chemistry analyses of samples B100, obtained of different oil (soya, sunflower and canola) and samples mixtures biodiesel+diesel, obtained ethanolic route for process of transesterification of soya oil. Basic analyses chemical of B100 obtained ethanol route were compared with methanol route. The process of biodiesel transesterification and glycerin separation obtained by methanol route is very quickly ompareted with ethanol route, can not forget the degree of toxicity of methanol and the high cost of methanol in Brazil. The results of color, density, flash point were almost the same within the experimental precision, but the infrared spectral of the samples of B100, in the two cases presented distinct peaks. The chemical analysis of samples of B100, via ethanol route from different oils, has presented different colors and densities, may cause changes of color in the final product, observed that color stipulated by ANP is red. Analysis of samples of B100, made before and after the step of washing and neutralized the pH, showed that the analyses required by the ANP for business this fuel, not relevant differences, allowing produce B100 with less cost, however the omission this step, could lead to oxidation of parts of the automobile, causing damage to consumers and future environmental and economic impact to the country.